On interim information and the information content of firm earnings: A state variable approach* - DONTOH, ALEX; RICHARDSON, GORDON (Contemporary Accounting Research, 1988)
This paper uses a state variable characterization of firm earnings to develop an economic model of interim information and its effects on the information role of announced earnings. The model provides a simple yet rigorous approach for assessing, both theoretically and empirically, the potential effects of interim information about non firm‐specific state variables on the information role of announced earnings. It is shown that, under appropriate conditions, uncertainty about firm earnings can be decomposed into uncertainty about firm‐specific and non firm‐specific state variables. This decomposition provides economic structure to the meaning of interim information. It is demonstrated, both in the theoretical and empirical analyses, that the interim revelation of industry‐wide state variables diminishes the information role of announced earnings. Résumé. L'auteur utilise une variable caractérisant la situation de l'entreprise au chapitre des bénéfices (variables d'état), en vue d'élaborer un modèle économique de l'information périodique et de ses conséquences sur le rôle informatif des bénéfices déclarés. Le modèle, simple mais rigoureux, permet d'évaluer, en théorie aussi bien qu'en pratique, les conséquences que peut avoir l'information périodique relative aux variables d'état qui ne sont pas spécifiques à l'entreprise (mais spécifiques au secteur) sur le rôle informatif des bénéfices déclarés. Il est démontré que, dans des circonstances appropriées, l'incertitude relative aux bénéfices de l'entreprise peut être décomposée en incertitude relative aux variables d'état spécifiques à l'entreprise et non spécifiques à l'entreprise. Cette décomposition donne une structure économique au sens de l'information périodique. Les études tant théoriques qu'empiriques démontrent que la communication périodique des variables d'état de tout un secteur diminue le rôle informatif des bénéfices déclarés.